Effect of Managerial Ownership, Leverage, Firm Size and Profitability on Accounting Conservatism - Solichah, Nur; Fachrurrozie, Fachrurrozie (Accounting Analysis Journal, 2019)
This study aims to obtain empirical evidence about the effect of managerial ownership, leverage, firm size, and profitability on accounting conservatism. The population of this study were 149 manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2014 until 2016. The number of samples used was 82 companies with a unit of analysis of 246. The selection of research samples using purposive sampling method. The analytical tool used to test the hypothesis is multiple regression analysis using IBM SPSS 23. The results of this study prove that managerial ownership, leverage, firm size, and profitability simultaneously influence accounting conservatism. The hypothesis testing partially shows that the size of the company has a significant positive effect on accounting conservatism. Profitability has a significant negative effect on accounting conservatism. Meanwhile, managerial ownership and leverage have no significant effect on accounting conservatism. Conclusions in this study indicate that the greater the size of the company will increase the application of accounting conservatism while the greater the profitability will reduce the application of accounting conservatism in manufacturing companies.